Endogenous micropeptides as potential diagnostic biomarkers and therapeutic drugs - Zhong, Aixi; Li, Shuai; Zhang, Jingxuan; Zhao, Jingyuan; Yao, Chenhui (Frontiers in Pharmacology, 2025)
Micropeptides, these small proteins derived from non-coding RNA, typically consist of no more than 100 amino acids in length. Despite the challenges in analysis and identification, their various critical functions within organisms cannot be overlooked. They play a significant role in maintaining energy metabolism balance, regulating the immune system, and influencing the development of tumors, which also gives them a decisive impact on the occurrence and development of various diseases. This review aims to outline the role and potential value of micropeptides, introducing their tissue classification and distribution, biological functions, and mechanisms, with a focus on their potential as diagnostic markers and therapeutic drugs.